2019
DOI: 10.1186/s12943-019-1073-4
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-TKI resistance promotes immune escape in lung cancer via increased PD-L1 expression

Abstract: BackgroundThe ATLANTIC trial reported that higher PD-L1 expression in tumors was involved in a higher objective response in patients with EGFR+/ALK+ non-small cell lung cancer (NSCLC), indicating the possibility of anti-PD-1/PD-L1 therapy as a third-line (or later) treatment for advanced NSCLC. Therefore, the determination of status and regulatory mechanisms of PD-L1 in EGFR mutant NSCLC before and after acquired EGFR-TKIs resistance are meaningful.MethodsThe correlation among PD-L1, c-MET, and HGF was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(154 citation statements)
references
References 51 publications
3
149
1
1
Order By: Relevance
“…Using the ProcartaPlexHuman Cytokine/Chemokine/Growth Factor Panel and the ProcartaPlexHuman Immuno-Oncology Checkpoint Panel, we found that patients with lower baseline plasma HGF or IL-8 levels, or a decrease of plasma IL-8, or an increase of plasma TIM-3 or CD152 level at 8 weeks after treatment may bene t more from camrelizumab with apatinib. Recent studies showed that high serum levels of the c-MET ligand HGF correlated with increasing neutrophil counts, which was associated with poor responses to checkpoint blockade therapies (17)(18)(19)(20). IL-8 is secreted by malignant tumor and stroma cells across many different types of tumor, and is a member of the CXC chemokine family identi ed as a chemotactic factor for neutrophils (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Using the ProcartaPlexHuman Cytokine/Chemokine/Growth Factor Panel and the ProcartaPlexHuman Immuno-Oncology Checkpoint Panel, we found that patients with lower baseline plasma HGF or IL-8 levels, or a decrease of plasma IL-8, or an increase of plasma TIM-3 or CD152 level at 8 weeks after treatment may bene t more from camrelizumab with apatinib. Recent studies showed that high serum levels of the c-MET ligand HGF correlated with increasing neutrophil counts, which was associated with poor responses to checkpoint blockade therapies (17)(18)(19)(20). IL-8 is secreted by malignant tumor and stroma cells across many different types of tumor, and is a member of the CXC chemokine family identi ed as a chemotactic factor for neutrophils (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, acquired EGFR‐TKIs resistance promotes the immune escape of lung cancer by upregulating the expression of PD‐L1. PI3K/AKT, MAPK, NF‐Kappa B signaling pathway, and AP‐1 participate in the upregulation of PD‐L1 induced by different EGFR‐TKI resistance mechanisms 154 . Other studies have also confirmed that EGFR/ALK mutations in NSCLC models upregulate PD‐L1 expression by activating the PI3K‐AKT, MEK (Mitogen‐activated protein kinase kinase)/ERK(Extracellular signal‐regulated kinase) pathway 155 .…”
Section: Abnormal Signaling Pathway Transduction and Related Protein mentioning
confidence: 95%
“…Reverse transcription, quantitative real-time PCR and Western blotting were performed as described previously (31). Oligonucleotide primers used for SDPR and GAPDH (internal control) were as follows: SDPR: 5'-CTCCGACGCAACCATTT-3'(sense); 5'-CTTTCTTGAGGCTATCCACTT-3' (antisense); GAPDH:5'-AGAAGGTGGGGCTCATTTG-3' (sense); 5'-AGGGGCCATCCACAGTCTTC-3' (antisense); GAPDH: 5'-AGAAGGTGGGGCTCATTTG-3' (sense); 5'-AGGGGCCATCCACAGTCTTC-3' (antisense) (32). All the reactions were performed in triplicate for each sample.…”
Section: Reverse Transcription Quantitative Real-time Pcr and Westermentioning
confidence: 99%